CT reconstruction algorithm and low contrast detectability of phantom study: a systematic review and meta-analysis - Yusof, Nur Aimi Adibah; Abdul Karim, Muhammad Khalis; Mohd Asikin, Nursyazalina; Paiman, Suriati; Awang Kechik, Mohd Mustafa; Abd Rahman, Mohd Amiruddin; Mohd Noor, Noramaliza (Bentham Science, 2022)
Background: For almost three decades, computed tomography (CT) has been extensively used in medical diagnosis, which led researchers to conduct linking of CT dose exposure with image quality. Methods: In this study, a systematic review and a meta-analysis study were conducted on CT phantom for resolution study especially based on the low contrast detectability (LCD). Furthermore, the association between the CT parameter such as tube voltage and the type of reconstruction algorithm, the amount of phantom scanning affecting the image quality and the exposure dose were also investigated in this study. We utilize PubMed, ScienceDirect, Google Scholar and Scopus databases to search related published articles from the year 2011 until 2020. The notable keywords comprise “computed tomography”, “CT phantom”, and “low contrast detectability”. Of 52 articles, 20 articles are within the inclusion criteria in this systematic review. Results: The dichotomous outcomes were chosen to represent the results in terms of risk ratio as per meta-analysis study. Notably, the noise in iterative reconstruction (IR) reduced by 24%, 33% and 36% with the use of smooth, medium and sharp filters, respectively. Furthermore, adaptive iterative dose reduction (AIDR 3D) improved image quality and the visibility of smaller less dense objects compared to filtered back-projection. Most of the researchers used 120 kVp tube voltage to scan phantom for quality assurance study. Conclusion: Hence, optimizing primary factors such as tube potential reduces the dose exposure significantly, and the optimized IR technique could substantially reduce the radiation dose while maintaining the image quality.